Understanding the Impact of Oligomeric Polystyrene Side Chain Arrangement on the All‐Polymer Solar Cell Performance. Issue 2 (14th September 2017) - Kurosawa, Tadanori; Gu, Xiaodan; Gu, Kevin L.; Zhou, Yan; Yan, Hongping; Wang, Cheng; Wang, Ging‐Ji Nathan; Toney, Michael F.; Bao, Zhenan
Abstract: The introduction of oligomeric polystyrene (PS) side chains into the conjugated backbone is proven to enhance the processability and electronic properties of semiconducting polymers. Here, two series of donor and acceptor polymers are prepared with different molar percentages of PS side chains to elucidate the effect of their substitution arrangement on the all‐polymer solar cell performance. The observed device performance is lower when the PS side chains are substituted on the donor polymer and higher when on the acceptor polymer, indicating a clear arrangement effect of the PS side chain. The incorporation of PS side chains to the acceptor polymer contributes to the decrease in phase separation domain size in the blend films. However, the reduced domain size was still an order of magnitude larger than the typical exciton diffusion length. A detailed morphological study together with the estimation of solubility parameter of the pristine PS, donor, and acceptor polymers reveals that the relative value of solubility parameter of each component dominantly contributes to the purity of the phase separated domain, which strongly impacts the amount of generated photocurrent and overall solar cell performance. This study provides an understanding of the design strategies to improve the all‐polymer solar cells. Abstract : All‐polymer solar cells consisting of polystyrene (PS) oligomer side chain attached donor and acceptor polymers are investigated to reveal the effect of PS side chain substituted arrangement. An increase in domain purity and decrease in domain size are observed when the PS side chain is attached to donor and acceptor polymers, respectively, which mainly results from the solubility parameter of the polymers.